A comparison of the clinical usefulness of neck circumference and waist circumference in individuals with severe obesity. (2nd January 2017) - Assyov, Yavor; Gateva, Antoaneta; Tsakova, Adelina; Kamenov, Zdravko
ABSTRACT: Purpose/Aim : Neck circumference (NC) is an emerging anthropometric parameter that has been proposed to reflect metabolic health. The aim of the current study was to compare its clinical usefulness to waist circumference (WC) in the assessment of individuals with severe obesity.Materials and methods : A total of 255 subjects participated in the study. All anthropometric measurements were done by a single medical professional. Biochemical measurements included oral glucose-tolerance tests (OGTTs), fasting insulin, lipids, and hepatic enzymes.Results : The mean age of the participants was 49 ± 12 years with the mean body mass index (BMI) of 36.9 ± 6.2 kg/m 2 . Correlation analyses revealed that while WC was better associated with adiposity parameters, it was of little use in comparison to NC with regard to metabolic outcomes. In men, NC was positively associated with fasting plasma glucose, fasting insulin, FINDRISC scores . ROC analyses showed NC was better in distinguishing type 2 diabetes (AUC = 0.758; p < 0.001), insulin resistance (AUC = 0.757; p = 0.001), metabolic syndrome (AUC = 0.724; p < 0.001), and hypertension (AUC = 0.763; p = 0.001). Similar correlations were observed in women. Using binary logistic regression, we determined that a NC of ≥35 cm in women and ≥38 cm in men are valuable cut-off values to use in the everyday practice.Conclusion : In individuals with severe obesity, NC performs better than WC in the assessment of metabolic health.